2013
DOI: 10.1128/jvi.02421-12
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Glucocorticoid-Induced Leucine Zipper in Infectious Bursal Disease Virus (IBDV)-Induced Suppression of Type I Interferon Expression and Enhancement of IBDV Growth in Host Cells via Interaction with VP4

Abstract: Infectious bursal disease (IBD) is an acute, highly contagious, and immunosuppressive avian disease caused by IBD virus (IBDV). Although IBDV-induced immunosuppression has been well established, the underlying exact molecular mechanism for such induction is not very clear. We report here the identification of IBDV VP4 as an interferon suppressor by interaction with the glucocorticoid-induced leucine zipper (GILZ) in host cells. We found that VP4 suppressed the expression of type I interferon in HEK293T cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 54 publications
0
70
0
Order By: Relevance
“…However, while we found that only VP3 inhibits IFN-␤ expression by blocking the MDA5-dependent signaling pathway, we observed that viral protein VP4 also inhibits IFN-␤ expression. It is possible that VP4 inhibits IFN-␤ expression by interacting with host glucocorticoid-induced leucine zipper protein to block the nuclear translocation of NF-B p65 (16). These findings suggest that IBDV replication may employ different pathways to interfere with host antiviral innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, while we found that only VP3 inhibits IFN-␤ expression by blocking the MDA5-dependent signaling pathway, we observed that viral protein VP4 also inhibits IFN-␤ expression. It is possible that VP4 inhibits IFN-␤ expression by interacting with host glucocorticoid-induced leucine zipper protein to block the nuclear translocation of NF-B p65 (16). These findings suggest that IBDV replication may employ different pathways to interfere with host antiviral innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The VP3 protein binds the viral double-stranded (ds) RNA genome and is thought to block the interaction of MDA5 with the dsRNA, thereby inhibiting downstream events that culminate in type I IFN production [48]. In addition, the VP4 protein binds to the cellular glucocorticoid-induced leucine zipper (GILZ) protein, which inhibits the activation of nuclear factor kappa-enhancing binding (NF-KB) protein and activator protein-1 (AP-1) [49]. In mammalian cells, NF-KB and AP-1 cooperate with interferon regulatory factors (IRFs) 3 and 7 to stimulate type I IFN transcription.…”
Section: Discussionmentioning
confidence: 99%
“…pVP2 is further processed at its C-terminal domain by VP4 to generate the mature capsid protein VP2 (41 kDa) and four small peptides (21). A recent report indicates that VP4 is responsible for IBDV-induced immune suppression (22). The nonstructural viral protein VP5 only exists in IBDV-infected cells and plays different roles in IBDV-induced apoptosis during IBDV infection.…”
Section: Infectious Bursal Disease (Ibd) Is An Acute Highly Contagiomentioning
confidence: 99%